A parametric study on cyclic strength of coastal sand of Digha in West Bengal, India - Pinak Ray; Ramendu Bikas Sahu (International Journal of Geo-Engineering, 2021)
Abstract Stress controlled cyclic triaxial tests have been carried out on coastal sand of Digha, West Bengal, India at different frequencies, confining pressures, relative densities and number of loading cycles for determination of influence of these parameters on cyclic strength (expressed in terms of cyclic stress ratio) and initial liquefaction of Digha sand. The test results provide evidence that increasing density of sand increases liquefaction potential, though it has been found that increase in effective confining pressure reduces cyclic strength of sand. Cyclic strength of sand decreases with increase of number of loading cycles at a specific density and a particular confining pressure. It has been observed that frequency of loading cycles does have any significant influence on the number of cycles for initial liquefaction of Digha sand. An empirical correlation has been developed on cyclic strength of sand based on these parameters and it has been found that this correlation fits quite well with the observed experimental results.